Electron impact excitation of the 6p27s 4P1/2 state of bismuth from the ground state. (14th November 2016) - Marinković, B P; Predojević, B; Šević, D; Pejčev, V
Abstract: We have measured differential cross sections for electron impact excitation of the 6p 2 7s 4 P1/2 state of bismuth. The excitation is performed from the ground state at incident electron energies of 10, 20, 40, 60, 80 and 100 eV. Scattered-electron intensities are obtained in the angular range from 2° to 150°. The forward scattering function method is utilized for normalization. Integrated (integral, momentum transfer and viscosity) cross sections are determined by numerical integration of DCSs. The results are analyzed and compared with available experimental data.